Sebuah Refleksi Dan Introspeksi Budaya Dalam Journey International Openair Expressions 2008 Hiki - M. Dwi Marianto (Mudra Jurnal Seni Budaya, 2009)
Technically speaking, the journey and experience during the IOE 2008 participation in Japan can be seen as a subject of aesthetic-cultural reflection. In this case, there is no boundary line between the art works that were exhibited in the event with the phenomena of the city which was very greatly attracted the artist. The way how to see and to perceive the phenomena of the nature and culture presented, such as the city center atmosphere, the open space, the spontaneous behaveor of the public, and the city sreets,directly and indirectly, were influenced by the content of the references.